«Տեղեկատվական անվտանգություն» հասկացության էվոլյուցիան - Մկրտչյան Հայկուհի (YSU Journal of International Affairs, 2017)
In the middle of the 20th century, in the context of increasing role and volume of information, as well as the development of information technology, the threats to information security became much more complicated. As a result, the perception of information security has changed. If previously, the concept of "information security" was used in the context of the development of information and communication technologies to identify problems that arise through computer networks, now it has become more comprehensive, referring not only to the scope of technology.